The Analysis on Income of Beef Cattle Breeders in Various Crop Patterns in Umbulsari District, Jember Regency - Noer Soetjipto; Zaenal Fanani; Nanang Dwi Wahyono (Journal of Development Research, 2018)
The objective of research is: (1) to analyze the cost incurred at integrated farming involving beef cat-tle breeding and various crop patterns; (2) to estimate the revenue received from the integrated farm-ing involving beef cattle breeding and various crop patterns; (3) to find out the income obtained from the integrated farming involving beef cattle breeding and various crop patterns; and (4) to acknowledge the balance of revenue and cost of the integrated farming involving beef cattle breeding and various crop patterns. Research was located in Umbulsari District, Jember Regency, starting from 16 June 2016 to 28 September 2016. Sampling frame technique used in this research is Two-Stage Cluster Sampling. Both sampel and location of research are determined with purposive sampling. The analytical model of research is the analysis on cost and revenue of livestock-crop farming. Research indicates some results. (1) Crop Pattern 5, which cultivates sugarcane only, and beef cattle breeding have produced the heaviest cost of all combinations observed, especially if measured in terms of per hectare and per livestock unit. The cost for this crop pattern is IDR 96,750,000.- while the cost for beef cattle breeding is IDR 10,865,000.-. Total cost of both works attains IDR 107,615,000.-. The reason behind this huge cost is that Crop Pattern 5 involves high production cost to cover the costs of land processing, land lease, and organic fertilizer; (2) Crop Pattern 5 has produced the highest reve-nue. The revenue of this crop pattern per hectare is IDR 110,450,000.- while beef cattle breeding per livestock unit gives revenue at IDR 14,900,000.-. Total revenue then is around IDR 125,350,000.-; (3) The income obtained from Crop Pattern 5 is IDR 13,700,000.- whereas beef cattle breeding deliv-ers income around IDR 4,035,000.-. Total income is then IDR 17,735,000.-. (4) The highest balance between revenue and cost is 1.82 and it is found at Crop Pattern 4.